Optimization of medium and fermentation parameters for high cell density cultivation of azotobacter vinelandii - Then, Charles Khoon Thiam (2012)
Azotobacter vinelandii is a free-living N-fixing bacterium capable of converting atmospheric nitrogen into ammonia, a nitrogen source easily assimilated by plants. Although numerous researches have been done on the genetics and metabolism of A. vinelandii, little information on cell mass production for biofertilizer applications is available. Therefore, the objective of this research is to develop an industrial culture medium and a cultivation strategy for the mass production of A. vinelandii in a semi-industrial scale. Based on previous works, several media formulations were tested for their cell growth potential. The best medium yielded a cell mass of only 3.94 g L-1 in shake flask cultures and was optimized using both a classical and statistical approach, achieving a maximum cell mass of 7.71 g L-1 and 8.82 g L-1, respectively. The cell yield on glucose of the classically optimized medium was approximately 35.5% higher than the statistically optimized medium and was thus used in subsequent bioreactor experiments. Batch cultivations in 16-L stirred tank bioreactors with and without pH control yielded cell mass concentrations of 7.52 g L-1 and 15.86 g L-1 respectively. A series of fed-batch cultivations was carried out to determine the factors limiting cell growth. A combination of a constant feeding strategy coupled with pH and dissolved oxygen control with additional pure oxygen sparging was found to yield the highest cell mass concentration of 40.65 g L-1 in 16-L bioreactor cultivations. The cultivation in a 150- L stirred tank bioreactor revealed that oxygen is one of the most critical factors affecting cell mass production of the highly aerobic A. vinelandii. The decreased oxygen transfer rate limited cell growth but increased alginate production. The maximum cell mass obtained in a fed-batch culture of Azotobacter vinelandii in a 150-L stirred tank bioreactor was 28.35 g L-1 while the maximum alginate concentration was 18.60 g L-1.